Community power flow control for peak demand reduction and energy cost savings - Pholboon, Seksak; Sumner, Mark; Kounnos, Petros (2017)
The increase in penetration of renewable energy sources, such as solar or wind, and high peak load demand can cause grid network security issues. The incorporation of demand side management and energy storage devices can provide a solution to these problems. This paper presents a community power flow control (PFC) strategy which reduces peak grid demand, and increases self-consumption of renewable energy which produces energy cost savings in smart communities with grid-connected photovoltaic (PV) systems. The PFC aims to directly control high power consumption appliances and the charge/discharge of a community battery storage using measurement of the instantaneous power demands of the community. Historical data records of the community daily energy consumption and the available renewable energy are taken into account to manage the loads and battery storage. Simulation results show for a community of one hundred houses, with 114 kWp of PV arrays, and a 350kWh battery system that the percentage of the average peak power demand reduction over the year is 32%,whilethePV energy self-consumption increases by73%. This can produce an annual energy cost saving of up to £1100 when compared to the same community with only PV.